ARTISTIC INTERPRETATION OF HUMAN CONFLICT IN SHAKESPEARE’S WORKS: A STUDY OF HAMLET, MACBETH, AND OTHELLO (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the artistic interpretation of human conflict in William Shakespeare’s major tragedies, focusing on Hamlet, Macbeth, and Othello. It highlights how Shakespeare explores inner psychological struggles, moral dilemmas, ambition, jealousy, and emotional tension through complex characters and dramatic situations. The study emphasizes that Shakespeare’s representation of conflict is not limited to external actions but deeply rooted in the human mind. These tragedies reveal how conscience, power, and trust can shape human behavior, ultimately leading to both personal and societal destruction. The article concludes that Shakespeare’s works continue to influence modern understanding of human conflict due to their timeless psychological depth.